SP12RTS: a degree-12 model of shear- and compressional-wave velocity for Earth's mantle - Koelemeijer, P; Ritsema, J; Deuss, A; van Heijst, H (Oxford University Press, 2016)
We present the new model SP12RTS of isotropic shear-wave (Vs) and compressional-wave (Vp) velocity variations in the Earth’s mantle. SP12RTS is derived using the same methods as employed in the construction of the shear-wave velocity models S20RTS and S40RTS, and the same data types. SP12RTS includes additional traveltime measurements of P-waves and new splitting measurements: 33 normal modes with sensitivity to the compressional-wave velocity and 9 Stoneley modes with sensitivity primarily to the lowermost mantle. Contrary to S20RTS and S40RTS, variations in Vs and Vp are determined without invoking scaling relationships. Lateral velocity variations in SP12RTS are parametrised using spherical harmonics up to degree 12, to focus on long-wavelength features of Vs and Vp and their ratio R. Largelow-velocity provinces (LLVPs) are observed for both Vs and Vp. SP12RTS also features an increase of R up to 2500 km depth, followed by a decrease towards the core-mantle boundary. A negative correlation between the shear-wave and bulk-sound velocity variations is observed for both the LLVPs and the surrounding mantle. These characteristics can be explained by the presence of post-perovskite or large-scale chemical heterogeneity in the lower mantle.